Quadruple Series Equation InvolvingGeneralized- BatemanK- Functions (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Formal solution four series equation involving generalized Bateman k Functions is given is this paper.Finally, the solution of four series equation is reduceto Freadholm integrals equation of second timein one independent which can be solve by some numerical method.